Quality Matters in Early Childhood Education and Care: Finland 2012 - Taguma, Miho (OECD Publishing, 2012)
This report reviews quality in childhood education and care in Finland. It suggest strengths and point to areas for further reflection on current policy initiatives
Keywords: Education; Finland